2016
DOI: 10.3171/2015.4.jns15194
|View full text |Cite
|
Sign up to set email alerts
|

Quality of survival the 1st year with glioblastoma: a longitudinal study of patient-reported quality of life

Abstract: OBJECT By exploring longitudinal patient-reported health-related quality of life (HRQoL), the authors sought to assess the quality of survival for patients in the 1st year after diagnosis of glioblastoma. METHODS Thirty unselected patients ≥ 18 years who underwent primary surgery for glioblastoma in the period 2011–2013 were included. Using the generic HRQoL questionnaire EQ-5D 3L, baseline HRQoL was assessed before surgery and at postoperative follow-up after 1, 2, 4, 6, 8, 10, and 12 months. RESULTS There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 46 publications
2
36
0
1
Order By: Relevance
“…Recent meta-analysis by Coomans et al [ 30 ] demonstrated that some HRQOL variables were independent predictors of overall patient survival and progression-free survival in glioma patients. Significant correlation was reported between deterioration of HRQOL scores and tumor progression in glioblastoma patients in longitudinal studies [ 31 ]. Thus, HRQOL is a very informative outcome measure as it reflects the subjectively perceived burden of tumor-related symptoms at the moment of assessment, and also, it has predictive value for long-term overall survival prognosis [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-analysis by Coomans et al [ 30 ] demonstrated that some HRQOL variables were independent predictors of overall patient survival and progression-free survival in glioma patients. Significant correlation was reported between deterioration of HRQOL scores and tumor progression in glioblastoma patients in longitudinal studies [ 31 ]. Thus, HRQOL is a very informative outcome measure as it reflects the subjectively perceived burden of tumor-related symptoms at the moment of assessment, and also, it has predictive value for long-term overall survival prognosis [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…So far, this has been investigated only in survivors of childhood brain cancer [6], preoperatively in adults with intracranial tumors using a cross-sectional design [33], as well as in some retrospective studies evaluating SI in mixed cancer populations [5]. Even though prospective studies on anxiety, depression, and quality of life after surgery are available [20,37], to our knowledge, no prospective, controlled, observational studies have been conducted previously, with emphasis on SI in patients with primary intracranial tumors. Therefore, we investigated the incidence of SI and depression, their relation with HRQoL and social support as a possible protecting factor in patients with brain tumors over the first 9 months after diagnosis.…”
Section: Introductionmentioning
confidence: 97%
“…Patients with glioblastoma present with a variety of symptoms and signs, such as neurological deficits and epileptic seizures, cognitive problems and neuropsychiatric symptoms of anxiety and depression, caused by the tumor itself, tumor-related treatment, or a combination of these factors [6]. These symptoms may all have a negative effect on the health-related quality of life (HRQoL) [7,8], leading to inactivity [7] and the ability to continue a normal working life [7,9]. The patient's accelerating symptoms may also affect the nearest relative's HRQoL [10].…”
Section: Introductionmentioning
confidence: 99%